The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1111/j.1365-2141.2000.02434.x
|View full text |Cite
|
Sign up to set email alerts
|

Minimal residual disease studies are beneficial in the follow‐up of TEL/AML1 patients with B‐precursor acute lymphoblastic leukaemia

Abstract: Summary. The t(12;21)(p13;q22) translocation has been identified as the most common chromosomal abnormality in childhood acute lymphoblastic leukaemia (ALL). Initially, several investigators reported an excellent prognosis in paediatric leukaemias with this translocation, but other studies showed a 20% incidence in relapsed ALL. We performed an extensive analysis of 90 ALL patients. In 17 (19%) cases a TEL/AML1 fusion was found. However, this group was not representative as it included a high number of relapse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Most studies on the prognostic implications of t(12;21) have not reported individual data on gender and time in remission. However, the information that can be retrieved from studies providing pertinent data (Nakao et al , 1996; Harbott et al , 1997; Lanza et al , 1997; Satake et al , 1997; Loh et al , 1998; Rubnitz et al , 1999; Codrington et al , 2000; de Haas et al , 2000; Seeger et al , 2001; Tsang et al , 2001; Alvarez et al , 2005; Al‐Sweedan et al , 2007) does not support that boys generally relapse later than girls; based on all studies referred to above, the median remission duration before relapse was 37 months (range 17–102) for boys and 32 months (range 11–109) for girls. Thus, our finding may well be fortuitous and should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on the prognostic implications of t(12;21) have not reported individual data on gender and time in remission. However, the information that can be retrieved from studies providing pertinent data (Nakao et al , 1996; Harbott et al , 1997; Lanza et al , 1997; Satake et al , 1997; Loh et al , 1998; Rubnitz et al , 1999; Codrington et al , 2000; de Haas et al , 2000; Seeger et al , 2001; Tsang et al , 2001; Alvarez et al , 2005; Al‐Sweedan et al , 2007) does not support that boys generally relapse later than girls; based on all studies referred to above, the median remission duration before relapse was 37 months (range 17–102) for boys and 32 months (range 11–109) for girls. Thus, our finding may well be fortuitous and should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…La translocación del gen TEL puede ir acompañada por otras aberraciones genéticas secundarias, como deleción del otro alelo TEL, duplicación del gen de fusión o trisomía 21, observadas en 36% de los niños con LLA TEL/ AML1(+), los que tendrían un rol sinérgico con la proteína de fusión en la represión de la transcripción, influyendo en la progresión de la enfermedad [38][39][40][41][42][43] . El porcentaje de recaída medular de 23% observado en el grupo TEL/AML1(+), está en concordancia al publicado por De Haas (23%) en una serie de 17 pacientes TEL/AML1(+) 44 . La SLE estimada a 40 meses, aunque es levemente mayor en el grupo TEL/AML1(+) que en el grupo TEL/ AML1(-) (63% y 54%, respectivamente), no es estadísticamente significativa, hallazgo concordante con algunos estudios que no muestran diferencia significativa en la SLE de pacientes TEL/AML1 positivo y negativo 45 .…”
Section: Discussionunclassified
“…Several large prospective clinical MRD studies have shown that it is important to determine precisely the level of MRD for discrimination between low‐ and high‐risk patients (Cave et al , 1998; Coustan‐Smith et al , 1998; van Dongen et al , 1998). Quantitative analysis of MRD by real‐time quantitative polymerase chain reaction (RQ‐PCR) has contributed to accurate MRD analysis (Pongers‐Willemse et al , 1998; de Haas et al , 2000a; Verhagen et al , 2000). Two different types of PCR targets can be used: clone‐specific antigen receptor rearrangements and the breakpoint fusion regions of chromosome aberrations.…”
mentioning
confidence: 99%